Comparison of an anaerobic feed and split anaerobic–aerobic feed on granular sludge development, performance and ecology. (April 2017) - Thwaites, Benjamin J.; Reeve, Petra; Dinesh, Nirmala; Short, Michael D.; van den Akker, Ben
Abstract: The retrofitting of existing wastewater sequencing batch reactors (SBRs) to select for rapid-settling aerobic granular sludge (AGS) over floc-based conventional activated sludge (CAS), could be a viable option to decrease reactor cycle time and increase hydraulic capacity. Successful CAS-to-AGS conversion has previously been shown to be highly dependent on having a dedicated anaerobic feed, which presents additional engineering challenges when retrofitting SBRs. In this study we compared the performance of a split anaerobic–aerobic (An–Aer) feed with that of a traditional dedicated anaerobic feed regarding AGS formation and stability, nitrogen removal performance and microbial ecology. Using pilot trials, we showed that AGS could be established and maintained when using a split An–Aer feed at low organic loading rates analogous to that of a parallel full-scale conventional SBR. Additionally, we showed that AGS start-up time and nitrogen removal performance were comparable under a split An–Aer feed and dedicated anaerobic feed. Microbial ecology characterisations based on whole-of-community 16S rRNA profiles and targeted analysis of functional genes specific for nitrifying and denitrifying microorganisms, showed that the two different feed strategies had only subtle impacts on both the overall community composition and functional ecology. A much greater divergence in microbial ecology was seen when comparing AGS with CAS. Data presented here will be of value to those planning to retrofit existing CAS-based SBRs to operate with AGS and demonstrates the viability of using a more cost-effective split An–Aer feed configuration over a dedicated anaerobic feed. Graphical abstract: Highlights: Two feeding strategies were compared for aerobic granular sludge SBR operation. Performance of split anaerobic–aerobic and dedicated anaerobic feeding was compared. Start-up, performance and microbial ecology were similar under both feed strategies. Aerobic granular sludge ecology was different to conventional activated sludge. Split anaerobic–aerobic feeding is a viable, cost-effective SBR retrofit solution.